2010
DOI: 10.1016/j.biopsycho.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A multi-modal approach to the study of attachment-related distress

Abstract: The present study investigated the relative contribution of bottom-up and top-down control to task selection in the voluntary task switching (VTS) procedure. In order to manipulate the efficiency of top-down control, a concurrent working-memory load was imposed during VTS. In three experiments bottom-up factors such as stimulus repetitions, repetition of irrelevant information and stimulus-task associations were introduced to investigate their influence on task selection. We observed that the tendency to repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 71 publications
2
48
3
1
Order By: Relevance
“…The researchers interested in attachment, examined the effects of early experiences and their influence on children's future interactions. These effects were also confirmed in adulthood emotion regulation strategies (e.g., Dewitte, Houwer, Goubert, & Buysse, 2010;Gresham & Gullone, 2012). These studies have shown that individuals with secure attachment reported lower levels of negative emotions and make safer relationships with others.…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…The researchers interested in attachment, examined the effects of early experiences and their influence on children's future interactions. These effects were also confirmed in adulthood emotion regulation strategies (e.g., Dewitte, Houwer, Goubert, & Buysse, 2010;Gresham & Gullone, 2012). These studies have shown that individuals with secure attachment reported lower levels of negative emotions and make safer relationships with others.…”
mentioning
confidence: 57%
“…Attachment styles influence the emotion regulation strategies (e.g., Dewitte, Houwer, Goubert, & Buysse, 2010;Gresham & Gullone, 2012). People with secure attachment, because of having responsive and sensitive parents to their emotional state in childhood, have learned how to regulate their emotions and to communicate with others (e.g., Bowlby, 1969;Roque & Veríssimo, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with high levels of anxious attachment amplify stressful experiences and have greater levels of the stress hormone, cortisol, during acute laboratory stress tasks in young adults [4]. Recently, this pattern of cortisol reactivity was replicated in older anxiously attached adults across the day [5].…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, anxiously attached married individuals produce higher daily cortisol [30]. In young dating couples, women’s attachment avoidance predicts cortisol patterns as well [27,31]; for example, more avoidant female dating partners evidenced elevated cortisol before and during a conflict discussion with their dating partner followed by a rapid drop in cortisol immediately after the discussion, perhaps providing physiological relief once they were able to disengage from the discussion [27]. …”
Section: Attachment and Hpa Regulationmentioning
confidence: 99%